2010
DOI: 10.1590/s1413-86702010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B and hepatitis C markers among children and adolescents in the south brazilian region: metropolitan area of Florianópolis, Santa Catarina

Abstract: Hepatitis B and C are important causes of morbidity and mortality worldwide. In Brazil, according to the Ministry of Health, about 15% of population is infected by hepatitis B virus (HBV) and less than 1% by hepatitis C virus (HCV). Nevertheless, the age-specific prevalence of HBV and HCV markers remains unknown. This study aimed to determine the seroprevalence of HBV and HCV markers of infection and immunity in children and adolescents between 10 to 16 years old who live in the metropolitan area of Florianópo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In this study, a low prevalence of HBV infection of 1.1% was verified, similar to that of adolescents and young adults from developed countries, where hepatitis B vaccination programs are fully implemented, such as Italy (0.9%) 19 , Spain (0.9%) 20 and the United States (1%) 21 , and that verified in a nationwide study in northeastern and central-western Brazil (1.3%) 22 and by our group in the metropolitan area of Florianópolis, Santa Catarina, Brazil (0.5%) 23 . In contrast, this prevalence is lower than that of Greece (2.5%) 24 and of developing regions, where HBV vaccination programs are only partially implemented or not implemented at all, such as Mexico (5%) 25 , Bolivia (6.9%) 26 and central Brazil (5.9%) 27 .…”
Section: Ethical Considerationssupporting
confidence: 82%
“…In this study, a low prevalence of HBV infection of 1.1% was verified, similar to that of adolescents and young adults from developed countries, where hepatitis B vaccination programs are fully implemented, such as Italy (0.9%) 19 , Spain (0.9%) 20 and the United States (1%) 21 , and that verified in a nationwide study in northeastern and central-western Brazil (1.3%) 22 and by our group in the metropolitan area of Florianópolis, Santa Catarina, Brazil (0.5%) 23 . In contrast, this prevalence is lower than that of Greece (2.5%) 24 and of developing regions, where HBV vaccination programs are only partially implemented or not implemented at all, such as Mexico (5%) 25 , Bolivia (6.9%) 26 and central Brazil (5.9%) 27 .…”
Section: Ethical Considerationssupporting
confidence: 82%
“…[23][24][25]29,30 However, it is important to point out that the comparison of results is difficult as the maintenance of anti-HBs titers may be influenced by the time elapsed since vaccination and the level of exposure to hepatitis B virus. 31 The rates of HIV-infected individuals who develop anti-HBs levels ≥10 IU/L after receiving the standard, accelerated, or four double-dose schedules are variable, ranging from 38.7% to 91.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in southern Brazil between 2009 and 2010 showed that the vaccination coverage of children and adolescents who were born after the hepatitis B vaccination was introduced was over 92% 32 and that the HBsAg and antiHBc prevalences were less than 1% and 10%, respectively [32][33][34][35] . Hepatitis B virus vaccination began in 1992 for children younger than fi ve years of age and subsequently expanded to health professionals, students, fi refi ghters, police and the military in 1994 and to adults under 20 years old in 2001 36 .…”
Section: Informed Written Consent Was Obtained From All Participantsmentioning
confidence: 99%